Need Assessment on Learning to Teach in Education 4.0 for 21st Century Students’ Learning English Classroom - Ika Erawati; Eka Dyah Puspita Sari (EDULANGUE, 2019)
Many studies address that students’ achievement is encouraged by the effect of teacher professional development. But translating professional development into students’ achievement rarely involves the needs of students. Since there is no one method of need assessment on learning to teach that could fit all situations, picturing students’ point of view of what an English teacher should have would contribute to the needs of teacher professional development. Therefore, this study attempted to reveal the essential issue on engineering students’ perception toward the learning to teach in Education 4.0 that teacher should comply. A descriptive study was conducted to describe and analyze the need of teacher professional development (TPD) for the students’ learning in the 21st century from students’ point of view. Interview and questioner were implemented to complete the objective of the study. The data collected which was gathered from 90 students as the population sample were analyzed into statistical analysis. Based on the finding, this current study clarified that teacher professional development, especially for English teachers in occupying 21st century students’ learning needed to meet the competency of pedagogic, professional, personality, and social. The finding also showed that professional competence needed to be more considered for teacher professional development. The result obtained of this study is expected to contribute to the existing literature on professional development of ELT teachers for engineering students and also open wide opportunity for future research to conduct further study.